The scar that takes time to heal: A systematic review of COVID-19-related stigma targets, antecedents, and outcomes - Zhou, Xiang; Chen, Chen; Yao, Yuewei; Xia, Jingtian; Cao, Limei; Qin, Xin (Frontiers in Psychology, 2022)
COVID-19, as a crucial public health crisis, has affected our lives in nearly every aspect. Besides its major health threats, COVID-19 brings severe secondary impacts, one of which is the rise of social stigma. Although numerous studies have examined the antecedents and outcomes of COVID-19-related stigma, we still lack a systematic understanding of who is being stigmatized during the COVID-19 pandemic, what exacerbates COVID-19-related stigma, and what impacts COVID-19-related stigma has on victims. Therefore, this review aims to provide a systematic overview of COVID-19-related stigma. With 93 papers conducted with 126,371 individuals in more than 150 countries and territories spanning five continents, we identify three targets that have received the most research: Chinese/Asian people, (suspected) patients and survivors, and healthcare workers. Furthermore, we find that for each stigma target, characteristics of the stigmatized, stigmatizer, and context contribute to COVID-19-related stigma and that this stigma negatively influences victims' health and non-health outcomes. We call for future research to provide a more integrative, balanced, and rigorous picture of COVID-19-related stigma via conducting research on neglected topics (e.g., contextual factors that contribute to stigma toward HCWs) and stigma interventions and using a longitudinal design. In practice, we urge governments and institutions (e.g., ministries of public health, hospitals) to pay close attention to stigma issues and to promote safe and inclusive societies.